Pregnancy outcome after double renal transplant in a secondary level hospital - Utekar, Tushar; Thomas, Sam; Almshwt, Majda; Rai, Birendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
A 28-year-old recent migrant with no pre-conception care booked at 18 weeks of pregnancy with history of double renal transplant on left side wherein the kidney being placed in left iliac fossa. She was on cyclosporine, azathioprine, methylprednisolone the later was tapered in the first 2 months of pregnancy and was started on low dose aspirin, she had uneventful antenatal period until after 36 weeks when she developed mild preeclampsia and rising creatinine, which was managed by reducing immunosuppressant’s dose and was restarted on prednisolone by discussion over telephone with nephrologist from neighbouring Regional Hospital. She had an elective LSCS at 38 weeks as requested and had a healthy male baby after steroid cover. Her intraoperative and postoperative period was uneventful as well.